CFD analysis of a scramjet combustor with cavity based flame holders. (March 2018) - Kummitha, Obula Reddy; Pandey, Krishna Murari; Gupta, Rajat
Abstract: Numerical analysis of a scramjet combustor with different cavity flame holders has been carried out using ANSYS 16 - FLUENT tool. In this research article the internal fluid flow behaviour of the scramjet combustor with different cavity based flame holders have been discussed in detail. Two dimensional Reynolds-Averaged Navier-Stokes governing(RANS) equations and shear stress turbulence (SST) k − ω model along with finite rate/eddy dissipation chemistry turbulence have been considered for modelling chemical reacting flows. Due to the advantage of less computational time, global one step reaction mechanism has been used for combustion modelling of hydrogen and air. The performance of the scramjet combustor with two different cavities namely spherical and step cavity has been compared with the standard DLR scramjet. From the comparison of numerical results, it is found that the development of recirculation regions and additional shock waves from the edge of cavity flame holder is increased. And also it is observed that with the cavity flame holder the residence time of air in the scramjet combustor is also increased and achieved stabilized combustion. From this research analysis, it has been found that the mixing and combustion efficiency of scramjet combustor with step cavity design is optimum as compared to other models. Highlights: Comparison is made for a scramjet with and without cavity flame holder. The residence time is increased with the presence of cavity flame holder. Step cavity design achieved optimum performance.